2020
DOI: 10.1027/1614-0001/a000314
|View full text |Cite
|
Sign up to set email alerts
|

Core Self-Evaluations Over Time

Abstract: Abstract. Core self-evaluations (CSEs) represent a prominent construct with links to a number of important organizational behaviors and outcomes. Previous research on this variable appears to have assumed that CSE is a stable trait. However, very little research has examined this assumption, particularly over longer time periods. This study investigated this issue, focusing on within-person variability in CSE. Drawing from several theoretical perspectives related to self-concept, we examined the extent to whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Young adulthood is a transitional period between adolescence and adulthood; in this period, individual self-consciousness develops significantly, but it is easy to be influenced by others. Research showed that core self-evaluations will fluctuate over time due to changes in perceptions of social value and acceptance in interpersonal relationships [ 7 ]. Good core self-evaluations are of great significance to college students’ academic and healthy development [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Young adulthood is a transitional period between adolescence and adulthood; in this period, individual self-consciousness develops significantly, but it is easy to be influenced by others. Research showed that core self-evaluations will fluctuate over time due to changes in perceptions of social value and acceptance in interpersonal relationships [ 7 ]. Good core self-evaluations are of great significance to college students’ academic and healthy development [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, core self‐evaluations is a singular construct composed of self‐esteem, generalized self‐efficacy, non‐neuroticism, and locus of control and can be used as a focused area of research to improve person‐environment fit and encompasses individual factors to improve overall integration as well as successful employment outcomes (Jiang et al., 2017). Recent research has shown improvement in core self‐evaluations over time with changes in social value and acceptance (Tocci et al., 2020).…”
Section: Introductionmentioning
confidence: 99%